Introduction. Issue 3 (1st September 2020) - Karolewski, Ireneusz Pawel; Pänke, Julian; Roose, Jochen
Abstract : Germany's role in Europe and the world is changing fundamentally. For about five decades West Germany's and reunited Germany's position was very much aligned with the European integration project. Despite its hegemonic potential, Germany defined its role as a partner of the other EU member states. Within the EU framework and globally, it mostly acted jointly with European partners, particularly France. Although Germany's situation altered significantly after unification, it still refrained from exercising its increased power and was rather seeking the role of a "gentle giant." This was largely the case despite some exceptions, such as the unilateral recognition of Croatian and Slovenian independence in the early 1990s, and criticism that Germany might tend to single-handed foreign policy—the "Alleingang."